Synthesis, characterization and biological activities of tridentate ons Schiff bases and their mixed-ligand metal complexes containing imidazole or benzimidazole - Mazlan, Nurul Ain (2014)
Breast cancer is the most common cancer diagnosed and the second leading cause of cancer death among women after lung cancer. This fact had led the researchers to continuously synthesize new drugs to treat breast cancer. Thus, with this aim, new mixed-ligand metal complexes have been synthesized and evaluated for their biological activities in this research. Three series of tridentate Schiff bases derived from 4-methyl-3-thiosemicarbazide, 4-ethyl-3-thiosemicarbazide and 4-phenyl-3-thiosemicarbazide were synthesized using three aldehydes via condensation reactions, to form tridentate Oxygen-Nitrogen-Sulphur (ONS) containing ligands. The Schiff bases were then complexed with the imidazole or benzimidazole and Cu(II) and Ni(II) salts to produce new mixed-ligand transition metal complexes. These compounds were characterized by elemental analysis, molar conductivity,magnetic susceptibility and various spectroscopic techniques including Fourier- Transform Infrared (FT-IR), Nuclear Magnetic Resonance (NMR),UltraViolet/Visible (UV/Vis) and Inductively Coupled Plasma – Atomic Emission Spectroscopy (ICP-AES) analyses. The elemental analyses support the proposed formulae for the synthesized compounds while the molar conductance values indicated that the metal complexes were essentially non-electrolytes in DMSO solution. The magnetic susceptibility measurements and spectral results support the four-coordinate (square planar) geometry in which the Schiff bases behave as the tridentate ONS donor ligand coordinating via the hydroxyl oxygen, azomethine nitrogen, and thiolo sulphur atom while the imidazole or benzimidazole coordinates as a unidentate N-donor ligand. Single Crystal X-ray crystallographic analysis of five new mixed-ligand Cu(II) and Ni(II) complexes containing imidazole or benzimidazole shows that the complex exhibit a distorted square planar structure. The Schiff bases and their metal complexes have been evaluated for their biological activities against estrogen receptor positive breast cancer cell line (MCF-7) and estrogen receptor negative breast cancer cell line (MDA-MB-231). All of the Cu(II) complexes from salicylaldehyde and 3-methoxy salicylaldehyde derivatives with five Ni(II) complexes showed marked cytotoxicity against the cell lines while all except MTSali Schiff bases and most Ni(II) complexes were found to be inactive.